THE INFLUENCE OF TOURISM SECTOR ON GDRP (CASE STUDY : MALANG RAYA 2012-2021) - Iqbal Anhar, Adrizal
The tourism sector plays an important role in boosting a country's economy, in reducing unemployment and increasing productivity. After the Covid 19 pandemic, the current economic growth in Indonesia continues to flourish and shows improvement figures in increasing the country's income or currency. One of the areas in Indonesia that has the potential of the tourism sector is Malang Raya. Malang Raya is an area in East Java Province that includes Malang City, Malang District, and Stone City. The purpose of this survey is to test and analyze the impact of the number of tourists, number of sights, and number of hotels and population (dummy) on the poor PDRB. The approach in this study is a quantitative approach, over a 10-year period, from 2012 to 2021. This type of research uses associative research. The type of data used in this study is secondary data, which is Time series data from the period 2012-2021, and uses the method of ordinary least square regression equation with Degree of Freedom ? 5%. The analysis in the study uses panel data which is a combination of time- series data and latitude data. (cross section). Based on the results of the study, the number of foreign tourists has no influence on economic growth in Malang Raya, but the amount of domestic tourists influence the growth of the economy in malang Raya. The number of tourist attractions have a positive and significant impact on the economic growth of Malang Jaya, number of hotels and restaurants have a significant and positive impact on economic development in Malange Raya and the population has no impact on PDRB. Recommendation was given to the researcher to the government of Malanga Raya to be able to develop a number of attractions, make policies that are friendly to hotel business and rhetoric, and diversify tourist products, conduct more aggressive and effective marketing campaigns in the international market to raise awareness and interest in tourist objects in Malangu Raya. This can be done through social media, participation in international tourist exhibitions, and cooperation with international travel agencies.